2016
DOI: 10.17576/mjas-2016-2006-25
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical and Biological Changes During Co-Composting of Model Kitchen Waste, Rice Bran and Dried Leaves With Different Microbial Inoculants

Abstract: Disposal of food waste either by land-filling or incineration will cause environmental pollution and engaged in high treatment cost. Composting can be a viable food waste management, however, less research works have focused on the degradation of small scale kitchen waste. In this study, co-composting of model kitchen waste, dried leaves and rice bran were inoculated with four different sources of microbial inoculants (MI) namely commercial Effective Microorganism (EM), Tempeh, Tapai, a mixture of Tempeh and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The results suggested that the utilisation of fermented food has a comparable effect and can substitute the commercialised effective microorganisms (EM) as a biofertiliser. The microbial inoculants from tempeh and tapai can degrade the food wastes and increase the germination index of radish seeds (Fan et al 2016).…”
Section: Role Of Lactic Acid Bacteria As Biodecomposer and Biostimulantmentioning
confidence: 99%
“…The results suggested that the utilisation of fermented food has a comparable effect and can substitute the commercialised effective microorganisms (EM) as a biofertiliser. The microbial inoculants from tempeh and tapai can degrade the food wastes and increase the germination index of radish seeds (Fan et al 2016).…”
Section: Role Of Lactic Acid Bacteria As Biodecomposer and Biostimulantmentioning
confidence: 99%
“…Agaricus bisporus wheat straw residues and rice straw and hulls. [15,16] Pleurotus sp. soybean straw, coffee pulp, corn fibre, cottonseed hulls, groundnut shells, and maize straw.…”
Section: Strains Residues Referencesmentioning
confidence: 99%
“…It was then stored at room temperature for 8 to 10 days, away from direct sunlight, and absorbed actinomycetes during activation at the top of the surface with a pleasant smell and a pH below 3.3~3.5. [15].…”
Section: Activation Of Effective Microorganisms (Em)mentioning
confidence: 99%
See 2 more Smart Citations